RANCANG BANGUN ALAT KHUSUS UNTUK MEMBUKA NUT YANG TERKOROSI - Rosalia, Citra Asti; Budiansyah, Irfan; Putri, Khaerani Tiara; Muktabar, Adi Kurnia; Luthfi, Moch. (P3M Politeknik Negeri Indramayu, 2025)
Aircraft are highly complex transportation modes, assembled from various components to ensure optimal safety and reliability. One of the small yet essential components frequently used in aircraft is the nut, which generally exhibits corrosion resistance due to its stainless steel 304 material. However, corrosion can still occur, particularly in areas such as the galley, landing gear, lavatory, and engine construction. This study aims to develop a specialized tool to facilitate aircraft maintenance by effectively removing corroded nuts. The tool was designed using CAD SolidWorks and manufactured through turning, grinding, milling, and welding processes. It operates by clamping the nut and applying impact force until the nut breaks, utilizing a sharp blade to destroy the nut without damaging surrounding aircraft components. Torque testing was conducted to measure the rotational force capacity for various nut sizes. The test results demonstrate that the developed tool can efficiently, safely, and effectively remove corroded nuts, thereby simplifying aircraft maintenance and reducing the risk of damage to other components.